Experimental investigation of rooftop solar chimney for natural ventilation - Al-Kayiem, H.H. (Asian Research Publishing Network, 2015)
Rooftop solar chimney functions to create natural ventilation of buildings. It is a solar driven device which induces buoyancy force through the chimney channel to updraft the air out of the building. The design parameter of the rooftop solar chimney would affect the ventilation performance. This paper presents experimental results of measurements carried out on a modified rooftop solar chimney, with double absorber surfaces, horizontal and vertical. The system performance was evaluated at various design configurations and different operational condition. Three designs were tested and compared. The first design, model 1 was the basic rooftop solar chimney which contain vertical absorber plate, room's air inlet and total air outlet. The second design, model 2 was with two inlets, from the room and from the ambient through horizontal absorber, and total air outlet. The third design, model 3 was two inlets, but with extra vertical absorber plate installed in the middle of the vertical air outlet passage. The results demonstrated that operating the chimney with ambient air inlet show the lowest performance. Model 3 which is the rooftop solar chimney with additional vertical absorber in the air outlet passage showed performance enhancement with 1.2 and 7.6 compared to model 1 and model 2, respectively. Â© 2006-2015 Asian Research Publishing Network (ARPN).